Improved ALE mesh velocities for complex flows. (29th June 2017) - Bakosi, Jozsef; Waltz, Jacob; Morgan, Nathaniel
Summary: A key choice in the development of arbitrary Lagrangian‐Eulerian solution algorithms is how to move the computational mesh. The most common approaches are smoothing and relaxation techniques, or to compute a mesh velocity field that produces smooth mesh displacements. We present a method in which the mesh velocity is specified by the irrotational component of the fluid velocity as computed from a Helmholtz decomposition, and excess compression of mesh cells is treated through a noniterative, local spring‐force model. This approach allows distinct and separate control over rotational and translational modes. The utility of the new mesh motion algorithm is demonstrated on a number of 3D test problems, including problems that involve both shocks and significant amounts of vorticity. Abstract : An arbitrary Lagrangian‐Eulerian method is presented for shock hydrodynamics in which the mesh velocity is computed by the irrotational component of the fluid velocity and excess compression of mesh cells is treated through a noniterative local spring‐force model. This allows separate control over rotational and translational modes of the mesh velocity. The new mesh motion algorithm is demonstrated on a number of 3D test problems, including problems that involve both shocks and significant amounts of vorticity.